Biodiversity assessment in compartment 6, Sungai Menyala Virgin Jungle Reserve, Negeri Sembilan - Ahmad, Nur Razanah (2016)
Virgin Jungle Reserve (VJR) in Peninsular Malaysia defines a network of small protected areas meant to serves as undisturbed areas of natural vegetation for scientific research. This study was conducted in two ha plot of Compartment 6, Sungai Menyala Virgin Jungle Reserve, Negeri Sembilan to describe the tree composition and assess its species diversity. It was expected that the biodiversity status on the study site reflects its definition of being untouched and protected. However, challenges like forest management problems and natural occurrences somehow contribute to the determination of current biodiversity status in study site. A total of 20 plots measuring 20 m x 50 m were set up to collect data, and data were analyzed using Paleontological Statistic (PAST) software to calculate species diversity and richness index. At the study plot, there were 322 trees with a total basal area of 38.6 m2, comprising 29 families, 40 genus and 54 tree species. The Dipterocarpaceae (12 species) was the most species-rich family. It dominated the forest by 69 % of the basal area, with Shorea leprosula as the most dominant species. The most important tree species valued by Importance Value Index (IVI) was Shorea parvifolia, followed by Porterandia anisophylla and Shorea leprosula. There were 29 unique tree species recognized within this Dipterocarp-dominated study area. Having a relatively high species diversity and species richness with low species evenness, this study area has profound importance in stabilizing natural ecosystem, especially to its local scales.